Anticorpos IgM e IgG contra Escherichia coli HS, citocina TGF- β, C3 e proteína C-reativa em pacientes HIV positivos - Mateus, Camila dos Santos (2018)
Chronic activation of the immune system is characteristic of progressive HIV infection. This may be related to viral replication and/or other causes, such as microbial translocation. The present work aims to evaluate markers which could represent altered immune response and to correlate them with the response to antiretroviral therapy in patients infected with HIV. A total of 130 patients attended in the HIV / AIDS Specialized Attention Service of the Nucleus of Medical and Integrated Attention, University of Fortaleza, were included in this study. The levels of IgG, IgM, IgG1, IgG2 antibodies were determined using a solid-phase immunoenzymatic method using lipopolysaccharide-rich Escherichia coli HS extract. C3, immunoglobulin G, IgM and C-reactive protein (CRP) determinations were performed by immunoturbidimetric method. Patients were classified into three groups: Group I: HIV patients without antiretroviral therapy (ART); Group IIA (aviremic): HIV patients who had complete viral suppression after one year of ART; Group II B (viraemic): HIV patients who presented incomplete viral suppression after one year of ART. Anti-E. coli HS IgM antibodies were significantly higher in the HIV-negative group compared to other groups (p <0.01) and also compared to viremic Group IIB it was even more significant (p <0.0001). Anti-LPS IgM titres correlated with total IgM levels in the HIV-negative group (r = 0.532, p = 0.0004) and aviremic Group IIA (r = 0.327, p = 0.001). Anti-LPS IgG and anti-E. coli HS IgG levels were higher in the HIV-negative group compared to viremic Group IIB (p = 0.05; p = 0.05). Anti-LPS IgG titres were correlated with total IgG serum levels in the HIV-negative group (r = 0.378, p = 0.016), Group I without therapy (r = 0.96, p = 0.002), and viremic Group IIB (r = 0.378, p = 0.00016). There was also a correlation between anti-E. coli HS IgG and CRP in individuals using ART (r = 024; p = 0.012). C3 levels were in the normal range for all groups; nonetheless, higher values were observed in the HIV-negative group than in the Groups I and IIA (p> 0.0001) and in the Group IIB (p = 0.05). TGF-β cytokine levels were significantly higher in the HIV-negative group when compared to the Group II A (p = 0.03). A correlation was observed between TGF-β and IgM anti- E. coli HS in Group I without therapy (r = -0.462; p = 0.027). We can suggest that the markers studied in the present study may somehow contribute to the follow-up of HIV positive individuals using ART. The markers are relatively low in cost and can be easily deployed in any clinical laboratory. Further studies with higher number of patients under ARV treatment are necessary to demonstrate their usefulness.